Green Power: Exploring the Nexus Between Renewable Energy and Foreign Direct Investment Flows - Lim Thye Goh; Siong Hook Law; Irwan Trinugroho (SAGE Open, 2025)
This study examined the impact of renewable energy adoption on the attractiveness of Asian emerging economies to Foreign Direct Investment (FDI) amidst 2020s global economic upheavals. Utilising an Autoregressive Distributed Lag (ARDL) cointegration bounds testing approach to analyse data from 1971 to 2020, the findings revealed a significant positive correlation between renewable energy use and long-term FDI inflows, particularly in Indonesia and Malaysia. Furthermore, the analysis has shed light on the positive impact of rising real per capita income on FDI attractiveness in Malaysia and the Philippines, suggesting a multifaceted economic landscape influencing investment trends. This research has distinguished itself by demonstrating how renewable energy initiatives, alongside economic indicators, have significantly attracted FDI in Asian emerging markets. It has highlighted the ASEAN 4 countries, especially Indonesia and Malaysia, with their rich renewable energy resources and supportive policies, increasingly favoured by global investors. This study’s contribution has been novel in its focussed analysis of the interplay between renewable energy adoption and FDI attractiveness, offering insightful implications for policymakers and investors. JEL Codes: F21, O11, Q43.